The Elimination of Overshoot Curve Response of Closed Loop in Proportional Integral (PI) Controller - Azwardi Azwardi; Cekmas Cekdin (IAES Indonesia Section, 2015)
Most operators in industry use trial and error methodin determining the parameter in PID controller. This way isquite dangerous because it cannot predict what will happen inthe next process. For this, we need a method that can adjust thechanging of parameter in process, and simultaneously retune theparameter of controller automatically. Ziegler-Nichols method, amethod for setting parameter of PID controller, can be use foreliminating the oscillation and reducing overshoot curve in aprocess. This method is common yet, but it offers simpleprocedure but produce quick and accurate result. This methodanalyzes the curve of a process. It is done when oscillation andovershoot projected onto x-axis (time) occurred. The parametersresulted from this analysis among others are: critical gain (Kpu),time/period oscillation (Tosc), static gain (K), proportional gain(Kp), integral time Ti, and differential time Td. These parameterswill be tuned to PID controller using Ziegler-Nichols method.The overshoot (Mp) curve response of closed loop in thissimulation is 0 %. It will save energy and time beside that thestability of system can be maintained.